PATRON-CLIENT RELATIONSHIP OF POLITICIANS AND BUREAUCRATS IN THE 2024 NORTH BUTON SIMULTANEOUS ELECTIONS - Malik , Muhammad Kurniawan; Arsyad, Armin; Rafiutdarajat , Wa Ode (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2025)
This research examines the patron-client relationship between politicians and bureaucrats in the implementation of the simultaneous regional elections in North Buton Regency in 2024, focusing on the influence of patronage patterns on bureaucratic politicisation and the dynamics of political support in the regional bureaucracy. The main objective of the research is to reveal patterns of patronage, forms of bureaucratic politicisation, and their impact on governance during the Pilkada process. The method used is a qualitative case study approach, with data collection through participatory observation, in-depth interviews, and documentation. Data were analysed using the Miles and Huberman model and thematic analysis techniques to identify patterns and main themes. The main findings reveal the formation of two patronage axes that split the bureaucracy into two competing political forces, where bureaucrats' loyalties are strongly influenced by patron-client relationships based on merit and political dependence. The politicisation of the bureaucracy is visible through the practice of abuse of authority, politicisation of social assistance programs, project distribution, recruitment of honorary employees, and transactional promotions. This finding is important because it illustrates how a strong patronage culture is a serious obstacle to bureaucratic professionalism and accountable local governance, as well as providing strategic recommendations for bureaucratic reform and strengthening ASN neutrality in local democracy.